SINTESIS SCAFFOLD ALGINAT-KITOSAN-KARBONAT APATIT SEBAGAI BONE GRAFT MENGGUNAKAN METODE FREEZE DRYING - M R Aufan (Jurnal Biofisika, 2012)
Scaffold is a three dimensional structure that can be used as temporary supporting media in body tissue repairmen process. Some properties that must be owned by the scaffold are porous, biocompatible, biodegradable, bioactive, and have sufficient mechanical strength to sustain the new tissue growth. In this present study, the scaffold will be synthesized for bone tissue repairmen using alginate, chitosan, and carbonate apatite. The variation ratio of alginate and chitosan used in this study was 100% alginate, 2:1. 1:1, 1:2, and 100% chitosan with the same mass of carbonate apatite for each variation, which is 0.1 gram. The results of mixing the three ingredients were then freeze-dried in order to obtain the porous characteristic of the scaffold. From the results of the FTIR, the crosslinking process between the carboxyl groups on alginate characterized by the emergence of the peak at 1620 cm-1 frequency and the ionic bonding between alginate and chitosan are observed. The results of SEM examination stated: first, the properties of porous scaffold is successfully acquired using freeze drying method; second, the variations in the composition of alginate and chitosan as well as the addition of carbonate apatite scaffold affect the structure formed. Composition of alginate: chitosan = 1:1 tends to produce a more dense scaffold compared with other compositions; third, the existence of carbonate apatite is observed on the surface of the scaffold.